2021
DOI: 10.3390/jcm10163536
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Risk-Adapted Venous Thromboembolism Prediction in Multiple Myeloma Patients

Abstract: Multiple myeloma (MM) is associated with an increased risk of venous thrombosis (VTE). In the United Kingdom Medical Research Council (MRC) XI study of patients treated with immunomodulatory therapy, the VTE rate was 11.8% despite 87.7% of the patients being on thromboprophylaxis at the time of thrombosis. In order to effectively prevent VTE events in MM patients, a better understanding of patient and disease risk factors that might predict thrombosis is required. We performed a retrospective cohort analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Nonetheless, studies have shown that risk of thrombosis is not completely abrogated by any of these thromboprophylaxis strategies. In fact, high rates of both venous and arterial thrombosis have been reported in patients with MM receiving therapy with immunomodulatory agents despite thromboprophylaxis 24–26 . Bradbury et al reported on the thrombosis rates observed in the Myeloma IX and Myeloma XI phase 3 trials and disappointingly, thrombosis incidence rates at 6 months remained >10% in the later trial despite much higher rates of thromboprophylaxis (80.5% vs. 22.3%) 25 .…”
Section: Thrombosis In Multiple Myelomamentioning
confidence: 99%
“…Nonetheless, studies have shown that risk of thrombosis is not completely abrogated by any of these thromboprophylaxis strategies. In fact, high rates of both venous and arterial thrombosis have been reported in patients with MM receiving therapy with immunomodulatory agents despite thromboprophylaxis 24–26 . Bradbury et al reported on the thrombosis rates observed in the Myeloma IX and Myeloma XI phase 3 trials and disappointingly, thrombosis incidence rates at 6 months remained >10% in the later trial despite much higher rates of thromboprophylaxis (80.5% vs. 22.3%) 25 .…”
Section: Thrombosis In Multiple Myelomamentioning
confidence: 99%
“…When individual variables from the Khorana score were subjected to univariate and multivariate analysis, the white blood cell count was the only variable that retained predictive significance. 43 .…”
Section: Thrombo-hemorrhagic Risk Factors and Risk Stratificationmentioning
confidence: 99%
“…The rate of VTE occurrence remains unacceptably high in MM patients with approximately 10% of patients developing a thrombosis during the course of their disease [21,22] . It has been demonstrated that thrombosis rates in patients with malignancy are highest in the first year following diagnosis and in particular, in MM, thrombosis rates appear to be highest in the first 3 months following diagnosis [1,13,22,23] . It is hypothesised that these initial high rates are due to both accelerated neoplastic activity, increased tumour burden and, with treatment initiation, there may be overwhelming release of procoagulant factors and cytokines once apoptosis ensues.…”
Section: Vte Rates Despite Thromboprophylaxis: Immunomodulatory Agentsmentioning
confidence: 99%
“…It has long been acknowledged that there is a strong association between cancer and thrombosis but the risk of these events varies widely across the spectrum of cancer subgroups. VTE rates remain high in patients with MM with almost 10% of patients suffering from thrombosis during their disease course [ 1 , 2 ] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation